2014
DOI: 10.1016/j.bone.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-based biopatterning of SDF-1β augments BMP-2-induced repair of critical size calvarial bone defects in mice

Abstract: Background A major problem in craniofacial surgery is non-healing bone defects. Autologous reconstruction remains the standard of care for these cases. Bone morphogenetic protein-2 (BMP-2) therapy has proven its clinical utility, although non-targeted adverse events occur due to the high milligram-level doses used. Ongoing efforts explore the use of different growth factors, cytokines, or chemokines, as well as co-therapy to augment healing. Methods Here we utilize inkjet-based biopatterning to load acellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 67 publications
4
55
0
Order By: Relevance
“…The combined scaffold did not produce better healing or more bone fill than the traditional delivery system. This outcome agrees with previous studies that found that the osteoinductive BMP2 along with an osteoconductive matrix such as ACS precipitates the greatest amount of bone growth [16, 25, 27, 31, 32]. Though we hoped that as in previous studies Talymed would precipitate denser bone growth, this did not occur when it was used with the ACS scaffold wounds [8, 9].…”
Section: Discussionsupporting
confidence: 91%
“…The combined scaffold did not produce better healing or more bone fill than the traditional delivery system. This outcome agrees with previous studies that found that the osteoinductive BMP2 along with an osteoconductive matrix such as ACS precipitates the greatest amount of bone growth [16, 25, 27, 31, 32]. Though we hoped that as in previous studies Talymed would precipitate denser bone growth, this did not occur when it was used with the ACS scaffold wounds [8, 9].…”
Section: Discussionsupporting
confidence: 91%
“…48 The current study presents new evidence on the importance of SDF-1β, newly recognized to be abundant in bone, in regulating BMSC-mediated osteogenesis in situ. Together with our recent reports showing SDF-1β-mediated BMP-2 healing of critical-size calvarial defects using osteoconductive matrices for local delivery 26,37 , this study supports the potential translational use of SDF-1β in bone defect repair. Future studies aim to investigate in vivo the mechanisms of SDF-1β’s modulatory effects in terms of BMSC homing, capture, and osteogenic induction of transplanted as well as endogenous stem cells and osteogenic lineage cells.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to mechanical cues, biochemical cues provided by the ECM or neighboring tissues and cells act in vivo to regulate and control cell fate [6165]. To better recapitulate the native cellular environment, it is important to design systems where cells can be exposed to an engineered presentation of bioactive molecules in a 3D microenvironment.…”
Section: Incorporation Of Gradientsmentioning
confidence: 99%